2021
DOI: 10.1186/s40359-021-00589-4
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and its relationship with social support in Iranian students during the COVID-19 pandemic

Abstract: Background In addition to physical problems, the COVID-19 crisis continues to impose serious psychological adverse effects on people's mental health, which plays a major role in the efficiency of every community. Students, especially medical sciences students, suffer from more stress as a result of exposure to COVID-induced stressors. It is, therefore, essential to measure mental health and its relationship with social support in medical sciences students during the COVID pandemic. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
4
19
0
Order By: Relevance
“…Consistent with past pandemic research, we also demonstrated that lack of social support from friends or family was associated with profiles characterised by higher distress levels [ 34 , 62 , 110 ]. Importantly, social support was the strongest and the most consistent predictor within the models, suggesting that for parents (not unique to only those with chronic diseases) receiving diminished help from friends or family was associated with higher levels of reported states of depression, anxiety and distress.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with past pandemic research, we also demonstrated that lack of social support from friends or family was associated with profiles characterised by higher distress levels [ 34 , 62 , 110 ]. Importantly, social support was the strongest and the most consistent predictor within the models, suggesting that for parents (not unique to only those with chronic diseases) receiving diminished help from friends or family was associated with higher levels of reported states of depression, anxiety and distress.…”
Section: Discussionsupporting
confidence: 89%
“…We also observed that a high level of stress was associated with the use of coping strategies based on seeking social support and understanding from other people. This finding seems at odd with literature showing that engaging in meaningful relationships is often associated with positive effects ( Ghafari, Mirghafourvand, Rouhi, & Osouli Tabrizi, 2021 ; Thoits, 2011 ). However, we might speculate that in the specific times of COVID-19 pandemic the coping strategy based on social support may detain a detrimental effect on psychological well-being as it reckons with the limitations to entertain social contacts due to the measures for contagion prevention.…”
Section: Discussionmentioning
confidence: 64%
“…While often assumed to be low-cost, interventions in this area, if targeting disadvantaged groups, required substantial resources in the form of professionals' and volunteers' time, whether from public health, social care or education services, and some required joined-up efforts from communities [29]. The complex mechanisms between social support and mental health have been subject to more recent studies, including studies concerned with the impact of the pandemic on social support [21,[30][31][32].…”
Section: Example 2: Mental Health and Social Supportmentioning
confidence: 99%